The 21st Century Skills of School Administrators Affecting the Academic Administration of Schools Under the Special Education Bureau, Group 7: The 21st Century Skills of School Administrators Affecting the Academic Administration of Schools Under the Special Education Bureau, Group 7 - Puttajaroen, Pattira; Pusitrattanavalee, Supattara (RATANABUTH JOURNAL, 2025)
The objectives of this thematic paper are as follows: 1) To study the skill level of school administrators in the 21st 2) To study the level of academic management of educational 3) To study the relationship between the skills of school administrators in the 21st century and the academic management 4) To study the variables that predict the skills of school administrators in the 21st century that affect the academic management of educational institutions It is a quantitative research. Stratified random sampling by school type proportion using simple random sampling method The sample group is 274 teachers working in educational institutions under the Office of Special Education Administration Group 7. The instrument used was a questionnaire. The reliability value was .994. The statistics used are Pearson’s correlation coefficient and stepwise multiple regression analysis. The results showed that 1) The skills of school administrators in the 21st century, are at a high level in all aspects. 2) Academic management of educational institutions the overall and individual aspects are at a high level in all aspects. 3) The relationship between the skills of school administrators in the 21st century and the academic management of educational institutions is generally very high as statistically significant at the level of .001. 4) The skills of school administrators in the 21st century that affect the academic management of educational institutions in 5 areas are the best predictive variables, namely the variables of critical thinking and creative thinking skills. Technology and digital skills, leadership skills, vision skills, communication skills. Together they can predict the academic management of the educational institution statistically significant at the level of .001 at the level of 85.2 percent, and can create a regression equation in the form of raw scores and standard scores as follows: Forecast equation in the form of raw score = .193 + .228 (X4) + .221 (X7) + .213 (X1) + .164 (X6) + .121 (X2) Prediction equation in standard score form = 285 (X4) + .226 (X7) + .211 (X1) + .166 (X6) + .137 (X2)